PENGARUH PENJUALAN BERSIH DAN MODAL KERJA BERSIH TERHADAP HARGA SAHAM - Intan Rahayu; Mia Febriyanti; Wawan Sukmana (JURNAL EKONOMI PERJUANGAN, 2022)
This reasearch aims to determine and analyze the effect of net sales and net working capital on stock prices in textile and garment sub-sector companies listed on the Indonesia Stock Exchange for the 2016-2021 period. The population in this study are all textile and garment sub-sector companies listed on the Indonesia Stock Exchange for the period 2016-2021. The sampling technique used is purposive sampling, so that the samples obtained are 6 Textile and Garment Subsector companies listed on the Indonesia Stock Exchange for the 2016-2021 period. The method used is quantitative with descriptive and associative approaches. Data collection techniques using documentation and literature study. The source of data in this study is secondary data obtained from www.idx.co.id. This research consists of descriptive statistical analysis testing, path analysis and hypothesis testing (t test and F test) using SPSS version 26. Stock Price, Net Working Capital partially have no significant effect on Stock Price, Net Working Capital is not able to mediate Net Sales to Stock Price, and Net Sales and Net Working Capital simultaneously have a significant effect on Net Working Capital.